Methodologies used in advertising creativity research (1965-2007) (Communication & Society, 2009)
This research studies the creativity articles published in the advertising Anglo-Saxon journals during the period 1965-2007. In fact, we examine 36 articles with content analysis method because we would like to determinate how creativity is important for academic advertising. For that reason, our aim is to know scientific methodologies used in advertising creativity researches. The results expose that empiric articles are more relevant than theoretical articles, and quantitative methodology is the most used. Furthermore, we find more number of creativity articles during the 1970 and 1989.